Bond-slip behaviour of the CFRP ribbed bars anchored with the innovative additional ribs in concrete. (15th April 2021) - Wang, Qiang; Zhu, Hong; Tong, Yixuan; Su, Weiqiang; Zhang, Pu
Abstract: This study presents an experimental investigation on the bond behavior of ribbed CFRP bars with the newly developed aluminium alloy additional ribs (ARs) anchorage system in concrete. According to the test results, it was found that the initial pressure established at the bar-ARs changes the bond transfer mechanism and generally contributed to the enhancement of the elastic bond, descending bond, ultimate bond, as well as the residual bond of the bar in concrete. Among all the bond improvement caused by the ARs, the elastic bond strength improvement was the most noticeable, which was up to 171% to 382.1%. Besides, the notch effect that injures the bar tensile strength and gives rise to the premature bar failure was observed to be associated with the use of the ARs. However, such adverse phenomenon can be alleviated or even avoided by increasing the number, or adjusting the spacing and locations of the ARs in the anchorage zone. Finally, based on the comparison among the existing models, a new bond-slip constitutive model was put forward. The results indicated that the proposed model had a high fitting accuracy and good applicability to depict the whole pull-out process for both the unanchored and anchored CFRP ribbed bars in concrete.